ANALISIS RESEPSI MASYARAKAT KELURAHAN TOMPOTIKKA KECAMATAN WARA KOTA PALOPO TERHADAP ISU POLITIK PILPRES 2024 PADA PEMBERITAAN METRO TV (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This research discusses the reception of the village community Tompotikka regarding reporting on political issues in the presidential election on Metro TV. The objective of this research is to identify the acceptance of the village community Tompotikka regarding reporting on political issues in the presidential election on Metro TV news This research uses a qualitative approach using the reception analysis method. Reception analysis is carried out in two stages, namely text analysis using Teun Van Dijk's model of critical discourse analysis knowing the trend in the content of Metro TV news texts regarding political issues 2024 Presidential Election. The second stage, reception analysis of Stuart's encoding and decoding Hall model, is to determine the position of audience acceptance of the reporting text Political issues for the 2024 Presidential Election on Metro TV news. Source of data in analysis The text of this research is the text of the Metro TV report on the program "Primetime News” edition The data collection technique for text analysis is using an analysis document, the data used is Teun van Dijk's data analysis model analyze text based on text dimensions, social cognition, and social context. The results of text analysis in this research describe the message delivered by Metro TV to the public regarding the political issue of the 2024 Presidential Election. Based on two reports that have been analyzed in text analysis from This research, Responding to this, the five informants tended to be different in responding to the political issues of the 2024 Presidential Election which is made possible by the existence of a diversity of cultural backgrounds, education, environment and experience that they have. The results of the reception analysis showed that the five informants In interpreting the message conveyed, tend to be in a dominant position hegemonic, namely fully agreeing with the message conveyed by Metro Tv, as well as the negotiated position which is the condition in which the informant accepted part of Metro Tv's news text and rejected its application part of the text of the announcement that was broadcast. In this study, no informants are in an oppositional position and are changing meaningfully contained in the text reporting political issues in the 2024 Presidential Election.